The Use of Partner Reading Strategy in Improving Reading Comprehension of The Eighth Grade Students of Junior High School at Sigi - Rizkina, Zidna; Mukrim; Andi Patmasari; Nur Sehang Thamrin (Institut Agama Islam Negeri Palopo, 2025)
The research aims to prove if the use of partner reading strategy can improve reading comprehension of the eighth grade students of SMP Negeri 20 Sigi. This research uses a quasi-experimental research design. The population of this research was class VIII students at SMP Negeri 20 Sigi consisting of 66 students from three classes. The sample was class VIII A as the experimental group and class VIII B as the control group. Sample selection was carried out randomly. Data was collected through a reading test administry as a pre-test and post-test. By applying a significance level of 0.05, the researchers found that the sig value obtained (p) was lower than alpha (a) (0.000<0.05). It means that the hypothesis is accepted or the use of partner reading strategy can improve the reading comprehension of class VIII students at SMP Negeri 20 Sigi.